2014
DOI: 10.1007/s00431-014-2405-4
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25-hydroxyvitamin D levels and bronchiolitis severity in Spanish infants

Abstract: The prevalence of hypovitaminosis D is high in Spanish infants with bronchiolitis. The severity of acute bronchiolitis increases with a decline in serum 25 (OH) D level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
16
0
5
Order By: Relevance
“…Recent studies 8,9 found low serum 25-hydroxyvitamin D levels in children with bronchiolitis. Other researchers 10,19 have shown that cord blood levels of 25-hydroxyvitamin D have a strong inverse association with ARIs during the first 3 months of life and with ARIs due to RSV during the first year of life.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies 8,9 found low serum 25-hydroxyvitamin D levels in children with bronchiolitis. Other researchers 10,19 have shown that cord blood levels of 25-hydroxyvitamin D have a strong inverse association with ARIs during the first 3 months of life and with ARIs due to RSV during the first year of life.…”
Section: Discussionmentioning
confidence: 98%
“…Also, serum vitamin D levels decrease in children with bronchiolitis, suggesting that vitamin D may play a role in the pathogenesis of bronchiolitis. 6,8,9 Belderbos et al 10 performed a prospective birth cohort study and reported that children who are vitamin D deficient at birth have a sixfold risk of developing RSV bronchiolitis in the first year of life. Previous data suggest that action to change the vitamin D status of mothers during pregnancy and/or vitamin D supplementation of infants could reduce the risk of RSV-associated bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, VD plays a prominent role in boosting innate immunity, regulating adaptive immunity, and strengthening airway mucosal responses. Previous epidemiological studies show consistent independent associations between lower circulating levels of 25‐hydroxyvitamin D (25(OH)D) during childhood and an increased risk of upper and lower RTIs, including tuberculosis, pneumonia, asthma exacerbations, and bronchiolitis . Moreover, data from a recent individual‐patient‐data meta‐analysis of clinical studies show that VD supplementation protects against acute respiratory infections .…”
Section: Introductionmentioning
confidence: 88%
“…Previous epidemiological studies show consistent independent associations between lower circulating levels of 25-hydroxyvitamin D (25(OH)D) during childhood and an increased risk of upper and lower RTIs, 8 including tuberculosis, 9 pneumonia, 10 asthma exacerbations, 11 and bronchiolitis. 12,13 Moreover, data from a recent individual-patient-data meta-analysis of clinical studies show that VD supplementation protects against acute respiratory infections. 14 Variations in regional solar radiation (SR), a proxy of a population's VD status, have been associated with seasonal and latitudinal changes in the incidence and severity of respiratory infections such as influenza and tuberculosis, 15,16 but the associations of SR with infant bronchiolitis incidence and severity have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda yapılan çalışmalarda RSV'ye bağlı gelişen akut bronşiyolitte, immünitenin gelişiminde de rolü olan D vitamini eksikliğinin önemli olduğu bildirilmiştir (11,14). Literatürde çocuklardaki ASYE ile D vitamini arasındaki ilişkiyi araştıran çeşitli çalışmalar bulunmaktadır (11,(15)(16)(17). Ancak ülkemizde bu konudaki çalışmalar az sayıdadır (15,16).…”
Section: Discussionunclassified